Recurring myositis ossificans traumatica of temporal muscle: A case report - Jović, Saša; Brajković, Denis; Borilović, Milena; Marjanović, Uroš; Brkić, Marko; Kozomara, Ružica; Stošić, Srboljub (Vojnosanitetski pregled, 2021)
Introduction. Myositis ossificans traumatica (MOT) refers to a benign, localized ectopic bone formation within skeletal muscle bundles related to a traumatic injury. MOT rarely affects masticatory muscles, and it represents a major diagnostic and therapeutic problem for clinicians. Currently, the treatment of choice is complete excision of the calcified mass after bone maturation and resection of the affected bone. Case report. A 47-year-old male presented with a month-long severe restriction of mouth opening that was followed by extraction of the right lower third molar tooth under local anesthesia. A computed tomography (CT) scan revealed ectopic bone formation in the right temporal muscle extending to the right coronoid process. Surgical excision of the calcified mass was performed. Six years after the surgery, the patient reported the same symptoms. The CT scan revealed a calcified mass of the right temporal muscle extending to the medial pterygoid muscle. The patient was reoperated, and sent for the postoperative physical treatment. Conclusion. MOT represents a major diagnostic and therapeutic challenge for surgeons due to unclear etiology and frequent recurrences after surgical treatment. Further research is needed to clarify the mechanisms of ossification in MOT in order to develop conservative treatment approaches.
Keywords: myositis ossificans; temporal muscle; oral surgical procedures; recurrence; treatment outcome